Lowering blood homocysteine with folic acid-based supplements: meta-analysis of randomised trials. - Clarke, R (2000)
The objective of this study was to determine the size of reduction in homocysteine concentrations produced by dietary supplementation with folic acid and with vitamins B12 or B6. Meta-analysis of individual data on 1114 people in 12 randomised controlled trials assessed the effects of folic acid-based supplements on blood homocysteine concentrations. Multivariate regression analysis was used to determine the effects on homocysteine concentration of different doses of folic acid and of the addition of vitamin B12 or B6. The results showed that the proportional and absolute reductions in blood homocysteine produced by folic acid supplements were greater at higher pre-treatment blood homocysteine concentrations (p<0.001) and at lower pre-treatment blood folate concentrations (p<0.001). After standardisation to pre-treatment blood concentrations of homocysteine of 12 micromol/L and of folate of 12 nmol/L (approximate average concentrations for Western populations), dietary folic acid reduced blood homocysteine concentrations by 25 percent (95% confidence interval 23%-28%; p<0.001), with similar effects in the range of 0.5-5 mg folic acid daily. Vitamin B12 (mean 0.5 mg daily) produced an additional 7 percent (3%-10%) reduction in blood homocysteine. Vitamin B6 (mean 16.5 mg daily) did not have a significant additional effect. In conclusion, typically in Western populations, daily supplementation with both 0.5-5 mg folic acid and about 0.5 mg vitamin B12 would be expected to reduce blood homocysteine concentrations by about a quarter to a third (for example, from about 12 micromol/L to 8-9 micromol/L). Large scale randomised trials of such regimens in high risk populations are now needed to determine whether lowering blood homocysteine concentration reduces the risk of vascular disease.